Group Self-Control Therapy as a Social Rehabilitation Model to Reduce Online Gaming Duration among Adolescents - Darusman, Mhd. Ricky; Hidayati, Diana Savitri; Maharani, Farah Diba (Fathana, 2025)
The phenomenon of excessive online gaming among adolescents has emerged as a growing social concern in the digital era. Such behavior can disrupt adolescents’ social, academic, and psychological functioning, highlighting the need for interventions that not only address maladaptive behavior but also restore the individual’s ability to play a positive role in society. This study aimed to examine the effectiveness of Group Self-Control Therapy as part of the social rehabilitation process in reducing online gaming duration among junior high school students. The participants were four male adolescents aged 13–14 years in Malang City who reported daily online gaming durations of 3–6 hours. Assessment techniques included interviews, observation, the Culture Fair Intelligence Test (CFIT) Scale 2B, and the Game Addiction Scale for Adolescents (GASA). The intervention was delivered in seven sessions, covering initial contracting, goal setting, problem identification, commitment building, implementation of self-control techniques (self-talk, physical guidance, situational inducement), evaluation, termination, and follow-up. Results demonstrated a significant reduction in online gaming duration, from an average of 3.3–5.8 hours to 1.7–2.2 hours/ day, alongside a decrease in GASA scores from the moderate to the low category. These changes were accompanied by improvements in social functioning, such as increased school participation, reduced verbal conflicts with peers, and enhanced family interactions. The findings support the use of Group Self-Control Therapy as a school-based social rehabilitation strategy to address digital addictive behaviors in adolescents.